A New Method for Solving Fully Fuzzy Multi-Objective Linear Programming Problems - Mitlif, Rasha Jalal (Iraqi Journal of Science, 2022)
In this paper we present a new method for solving fully fuzzy multi-objective linear programming problems and find the fuzzy optimal solution of it. Numerical examples are provided to illustrate the method.